DEVELOPMENT OF A CURRENT CONTROL ULTRACAPACITOR CHARGER BASED ON DIGITAL SIGNAL PROCESSING - Ahmad Saudi Samosir (Universitas Ahmad Dahlan, 2009)
Ultracapacitor usually use as a short-term duration electrical energy storage because it has several advantages, like high power density (5kW/kg), long lifecycle and very good charge/discharge efficiency. Unlike batteries, ultracapacitors may be charged and discharged at similar rates. This is very useful in energy recovery systems such as dynamic braking of transport systems. Here are a few characteristics of ultracapacitors that should be kept in mind when integrating/designing a charging system for the intended application. An ultracapacitor with zero charge looks like a short circuit to the charging source. Most of low cost power supplies fold back the output current in response to a perceived short circuit, making them unsuitable for charging of ultracapacitors. Ultracapacitors have a low series inductance allowing easy stabilizing with switch mode chargers. The RC time constant of passive charging networks is usually too long. Therefore, linear regulators are inefficient components for ultracapacitor charging. In this paper, the development of a current control ultracapacitor charger based on Digital Signal Processing (DSP) is presented.